Survival after aluminum phosphide poisoning with cardiotoxicity: a case report - Habtamu Mesele Gebray; Addisu Liknaw Chekol (Journal of Medical Case Reports)
Abstract Introduction Aluminum phosphide is a cheap and commonly used rodenticide that is also an effective solid fumigant and frequently used for grain preservation. The pill contains around 44% inert elements (ammonium carbonate) to avoid disintegration of the tablet, while the rest (about 56%) is aluminum phosphide. Because it is freely available on the market, it is one of the commonly used agents for self-poisoning in different parts of the developing world. Early signs of toxicity are manifested by shock and circulatory failure. Until now, no specific antidote is available. Aggressive supportive management is the key to survival in cases of aluminum phosphide poisoning. Case presentation We present a case of successful management of aluminum phosphide poisoning-induced cardiotoxicity with a favorable outcome in a 48-year-old Black African female patient who was taken to a private clinic 6 hours after intentional ingestion of two tablets of aluminum phosphide. She presented with repeated vomiting, restlessness, and confusion. Upon examination, the patient was drowsy, pale, cold, and clammy. She had nonrecordable blood pressure and radial pulsation. Glasgow Coma Scale was 14/15. Routine laboratory investigations and initial electrocardiogram were normal. Six hours after intensive care unit admission, the electrocardiogram showed atrial fibrillation with fast ventricular response, ST segment elevation, and inverted T-waves. Cardiac troponin level was elevated. With the diagnosis of acute aluminum phosphide poisoning with cardiotoxicity (acute myocardial infarction), hospital-based protocol was administered and medical treatment for myocardial infarction was given. She was discharged on the fourth day after full recovery. She came for regular follow-up visits and had normal clinical evaluation, electrocardiogram, and laboratory findings. Conclusion Exposure to phosphine gas released from aluminum phosphide fumigants increases the risk of major morbidity and mortality. The mortality due to aluminum phosphide poisoning is very high and variable. The use of magnesium sulfate to reduce cardiac arrhythmias and mortality is well documented, but there is no uniformity in dose or frequency of its administration worldwide. Limitations One of the limitations of this report is the nature of the case report, being a retrospective design, giving no chance to establish a cause–effect relationship. Arterial blood gas analysis, serum magnesium level, and cardiac computed tomography/magnetic resonance imaging modalities were not available in the town. The recommended gastric lavage with potassium permanganate solution was not used in this case, because potassium permanganate is not available in Ethiopia. The other limitation is that, as it is a case report from a single center, it may not be representative of the general population. These limitations might have a negative impact on the generalizability of the findings.